Techniques for Improving Speaking Fluency of Students - Sapkota, Sangita (Journal of NELTA, 2016)
This paper presents an action plan and its implementation for enhancing speaking fluency of the EFL learners of lower secondary level. It is based on an action research, which presents my students’ poor speaking fluency, my interventions and implementations. Similarly, it presents different techniques for developing English speaking proficiency, and their implication, effectiveness and ineffectiveness of them as well. It further shows the role of different techniques to help students for developing English speaking proficiency. Journal of NELTA, Vol. 21, No. 1-2, 2016, Page:113-120